Genome-scale model development and genomic sequencing of the oleaginous clade Lipomyces - Czajka, Jeffrey J.; Han, Yichao; Kim, Joonhoon; Mondo, Stephen J.; Hofstad, Beth A.; Robles, AnaLaura; Haridas, Sajeet; Riley, Robert; LaButti, Kurt; Pangilinan, Jasmyn; Andreopoulos, William; Lipzen, Anna; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The Lipomyces clade contains oleaginous yeast species with advantageous metabolic features for biochemical and biofuel production. Limited knowledge on the metabolic networks of the species and limited tools for genetic engineering have led to a relatively small amounts of research on the microbes. Here, a genome-scale metabolic model (GSM) of Lipomyces starkeyi NRRL Y-11557 was built using ortholog protein mappings to model yeast species. Phenotypic growth assays were used to validate the GSM (66% accuracy) and indicated that NRRL Y-11557 ready utilized diverse carbohydrates but had more limited catabolism of organic acids. The final GSM contained 2193 reactions, 1909 metabolites, and 996 genes, and was thus named iLst996. The model contained 96 of the annotated carbohydrate-active enzymes. iLst996 predicted a flux distribution in line with oleaginous yeast measurements and was utilized to predict theoretical lipid yields. 25 other yeasts in the Lipomyces clade were then genome sequenced and annotated. 16 of the Lipomyces species had orthologs for more than 97% of the iLst996 genes, demonstrating the usefulness of iLst996 as a broad GSM for Lipomyces metabolism. Pathways that diverged from iLst996 mainly revolved around alternate carbon metabolism, with ortholog groups excluding NRRL Y-11557 annotated to be involved in transport, glycerolipid, and starch metabolism among others. Overall, this study provides a useful modeling tool and data for analyzing and understanding Lipomyces species metabolism and will assist further engineering efforts in Lipomyces.